1993
DOI: 10.1042/bj2920289
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-dependent phosphorylation is involved in resistance to tumour necrosis factor-α-induced cytotoxicity in a human monocytoid cell line

Abstract: To investigate the mechanism underlying resistance to tumour necrosis factor-alpha (TNF alpha)-induced cytotoxicity, we have developed a human hybrid cell line, designated A10, derived from the fusion of human U-937 monocytoid cells and human monocytes, which expressed large numbers of TNF alpha receptors and yet remained highly resistant to TNF alpha. However, in the presence of the protein kinase C (PKC) inhibitors RO-31-7549 or RO-31-8220 (donated by Roche), these cells became sensitive to TNF alpha-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This is consistent with earlier reports that TNF can mimic the effects of PKC activators (22,30,31). Induction of PKC could be one of the cellular protective responses triggered by TNF.…”
Section: Figsupporting
confidence: 93%
“…This is consistent with earlier reports that TNF can mimic the effects of PKC activators (22,30,31). Induction of PKC could be one of the cellular protective responses triggered by TNF.…”
Section: Figsupporting
confidence: 93%
“…Nevertheless, the interaction of TNF with its receptors induces phosphorylation of several proteins, and inhibitors of protein kinases influence TNF sensitivity significantly, suggesting that protein phosphorylation plays a critical role in TNF signaling (Beyaert and Fiers, 1994;Vil-cek and Lee, 1991). Several protein kinases, including PKC, have been implicated in mediating TNF responses (Galeotti et al, 1993;Hamamoto et al, 1990;Johnson and Baglioni, 1988;Sampson et al, 1993;Schutze et al, 1990;Zhang et al, 1994). It has been demonstrated that TNF can resemble a PKC activator.…”
mentioning
confidence: 99%
“…It has been demonstrated that TNF can resemble a PKC activator. It can cause rapid production of DAG, activation of PKC, and phosphorylation of proteins (Kronke et al, 1992;Pusztai et al, 1993;Sampson et al, 1993;Schutze et al, 1990). TNF-stimulated protein phosphorylation could be blocked by PKC inhibitors (Sampson et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has shown that the inhibition of PKC activity can also induce apoptosis in p21 Ras ‐transformed cells (Chen and Faller, 1995; Chen et al, 1998b). Like NF‐κB, PKC has been shown to be protective against many forms of apoptosis (Sampson et al, 1993; Sato et al, 1993; Chmura et al, 1996; Wang et al, 1997; Weiss et al, 1997; Cheng et al, 1998; Dooley et al, 1998; Ruvolo et al, 1998; Shen and Glazer, 1998; Chen and Faller, 1999; Jun et al, 1999; Lan and Wong, 1999; Zhou et al, 1999), and may provide endogenous protection against p21 Ras ‐induced apoptosis. While the mechanisms by which p21 Ras provides protection against apoptosis are being elucidated, less is understood about how p21 Ras can induce apoptosis or sensitize cells to different apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%